2015
DOI: 10.3389/fpsyg.2015.01014
|View full text |Cite
|
Sign up to set email alerts
|

Do gender differences in audio-visual benefit and visual influence in audio-visual speech perception emerge with age?

Abstract: Gender and age have been found to affect adults’ audio-visual (AV) speech perception. However, research on adult aging focuses on adults over 60 years, who have an increasing likelihood for cognitive and sensory decline, which may confound positive effects of age-related AV-experience and its interaction with gender. Observed age and gender differences in AV speech perception may also depend on measurement sensitivity and AV task difficulty. Consequently both AV benefit and visual influence were used to measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Next, we found that Czech women and men differ in how they utilize the multimodal information in speech. Previous studies with different populations provide inconclusive findings on gender differences in visual cue reliance (Alm & Behne, 2015;Aloufy, Lapidot, & Myslobodsky, 1996;Irwin, Whaler, & Fowler, 2006;Tye-Murray et al, 2007b). With a large sample and appropriate modelling of individual variation across subjects and stimulus items, we detected a robust gender effect: Men rely exclusively on auditory information more than women do (53% vs. 24%), who in turn more often show audio-visual integration (60% vs. 34%).…”
Section: Discussionmentioning
confidence: 54%
“…Next, we found that Czech women and men differ in how they utilize the multimodal information in speech. Previous studies with different populations provide inconclusive findings on gender differences in visual cue reliance (Alm & Behne, 2015;Aloufy, Lapidot, & Myslobodsky, 1996;Irwin, Whaler, & Fowler, 2006;Tye-Murray et al, 2007b). With a large sample and appropriate modelling of individual variation across subjects and stimulus items, we detected a robust gender effect: Men rely exclusively on auditory information more than women do (53% vs. 24%), who in turn more often show audio-visual integration (60% vs. 34%).…”
Section: Discussionmentioning
confidence: 54%
“…In addition, studies have indicated that females have a stronger activation than males in brain areas associated with speech perception for AV stimuli (Ruytjens et al, 2006(Ruytjens et al, , 2007. Studies regarding sex differences in AV speech perception have reported that, for AV incongruent stimuli, females are more sensitive to the visual information than males, giving more visual matched and/or fusion responses (Alm & Behne, 2015;Aloufy et al, 1996;Irwin et al, 2006;Öhrström & Traunmüller, 2004). Furthermore, previous studies have found sex differences in visual influence and reported that females, irrespective of age, are better speech readers than males (Dancer et al, 1994;Strelnikov et al, 2009;Watson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, several psychoacoustical studies have observed gender differences in speech reading tasks, suggesting that female subjects were better speech-readers than males (Alm & Behne, 2015;Dancer et al, 1994;Irwin et al, 2006;Strelinikov et al, 2009). Alm and Behne (2015), performing a study on young adults, showed that female listeners had better speech-reading performance than male listeners, whereas no gender differences were found in audio-visual benefit or visual influence in the group. Irwin et al (2006) found that female listeners displayed significantly greater visual influence on heard speech than male listeners did for brief visual stimuli.…”
Section: Gender Differences In Speech Recognition In Noisementioning
confidence: 99%
“…Another key factor that has received even less attention in the literature is possible gender differences in speech recognition in noise performance among hearing-impaired hearing aid users. It is important to understand this possible gender difference, particularly as studies on speech recognition in noise generally fail to equalize the distribution of male and female listeners, which frequently skews strongly towards one sex (e.g., Alm & Behne, 2015;D'Alessandro & Norwich, 2007;Healy, Yoho, & Apoux, 2013;Irwin, Whalen, & Fowler, 2006;Klasner & Yorkston, 2005;Rogers, Harkrider, Burchfield, & Nabelek, 2003). Furthermore, potential gender difference in speech recognition in noise performance also needs to be considered because it may play an important role in determining the benefit of hearing aid signal processing algorithms (Akeroyd, 2008;Hagerman & Kinnefors, 1995;Souza et al, 2015) and developing programmes for clinical rehabilitation and speech recognition counselling.…”
Section: Gender Differences In Speech Recognition In Noisementioning
confidence: 99%
See 1 more Smart Citation